Synthesis and characterization of cellulose Nano fibers in enhancing the tensile stress properties of paper composites. - D, Sushmitha.; S, Srinath. (International Journal of Engineering and Technology, 2018)
In this contemporary work, synthesis of Nano cellulose was performed using microwave irradiation and Sonochemical approach. Experiments were conducted to know the synergetic effect on the synthesis of cellulose nanoparticles using a microwave at 700 watts for 1 minute and followed by Sonication having a power of 500W with probes size of 13mm. The Sawdust was first undergone pretreatment steps, then Consecutive treatments of extracted cellulose with combined equipment finally, gives Nano cellulose of particle size 68nm after 2 hours of sonication with 3% HCl. The tensile stress of the paper composites was increased exhibiting excellent mechanical properties when [5] wt% of nano-cellulose is added to the pulp for paper composites.Â Â